PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN MEDIA KARTU KATA - Purwanto Purwanto (MEDIA DIDAKTIKA, 2019)
This study aims to improve initial reading skills by using word card media for grade 1 students at SDN Kalipang, Sugio District, Lamongan Regency. This type of research is a collaborative classroom action research conducted in two cycles. The research subjects were grade 1 students totaling 10 students. Data collection techniques used 1) oral reading and written tests to understand reading, 2) observation, and 3) documentation. The data analysis technique uses descriptive statistical analysis, namely by looking for averages. The results of the study show that learning to read the beginning by using word card media can improve reading skills of grade 1 students at SDN Kalipang, Sugio District, Lamongan Regency. Reading skills in pre-action amounted to 61 and completeness was 40%, in cycle I increased to 67.5 with completeness 70%, increase in cycle II 73 with completeness of 90%.